2010
DOI: 10.1111/j.1750-3841.2010.01828.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography/Olfactometry and Electronic Nose Analyses of Retronasal Aroma of Espresso and Correlation with Sensory Evaluation by an Artificial Neural Network

Abstract: To develop a method for evaluating and designing the retronasal aroma of espresso, sensory evaluation data was correlated with data obtained from gas chromatography/olfactometry (GC/O, CharmAnalysis™) and from an electronic nose system αFOX4000 (E-nose). The volatile compounds of various kinds of espresso (arabica coffee beans from 6 production countries: Brazil, Ethiopia, Guatemala, Colombia, Indonesia, and Tanzania; 3 roasting degrees for each country: L values, 18, 23, and 26) were collected with a retronas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 30 publications
1
34
0
4
Order By: Relevance
“…2-propionylpyrrole (1H-Pyrrole) was found in roasted coffee (Toci & Farah, 2008), in green Mexican coffee (Cantergiani et al, 2001) and in black coffee beans (Agresti et al, 2008). Dimethyl trisulfide marked in our study by the e-nose was also shown in the study by Blank (2002) in roasted and ground coffee and in roasted coffee by Michishita et al (2010).…”
Section: Resultssupporting
confidence: 53%
“…2-propionylpyrrole (1H-Pyrrole) was found in roasted coffee (Toci & Farah, 2008), in green Mexican coffee (Cantergiani et al, 2001) and in black coffee beans (Agresti et al, 2008). Dimethyl trisulfide marked in our study by the e-nose was also shown in the study by Blank (2002) in roasted and ground coffee and in roasted coffee by Michishita et al (2010).…”
Section: Resultssupporting
confidence: 53%
“…An RA simulator (RAS) developed by Roberts and Acree (1995) as one of various mouth models (van Ruth et al, 1994;Roberts and Acree, 1995;Elmore and Langley, 1996) has been used to analyze coffee aromas (Michishita et al, 2010;Watanabe et al, 2012;Akiyama et al, 2014) and how the amount of milk added affects the aroma of coffee beverages (Akiyama et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…As known contributors the boquet of wines and beers, these monoterpenes are also likely to influence coffee flavour. Indeed, linalool is reported to contribute to a woody or flowery note in coffee depending on concentration (Bonnländer et al, 2006 (Blank et al, 1992); 3 (Michishita et al, 2010), 4 , 5 (Mosciano, 2016), 6 (Akiyama et al, 2007), 7 (Milo and Grosch); 8 (Belitz et al, 2009), 9 (Burdock, 2010), 10 (Salo, 1970), 11 , 12 (Buttery and Ling, 1997), 13 (Czerny et al, 2008), 14 (Holscher and Steinhart, 1992).…”
Section: Application Of Analytical Methods To Measure Key Aroma Volatmentioning
confidence: 99%
“…In an attempt to unlock the compositional basis of coffee flavour there have been numerous studies involving the extraction and analysis of the volatile profiles of coffee from green bean to roasted ground bean and brew, from espresso style to instant coffee (Akiyama et al, 2007, Akiyama et al, 2003, Blank et al, 1992, Borém et al, 2013, Czerny et al, 1996, Kumazawa and Masuda, 2003, Michishita et al, 2010, Ribeiro et al, 2009, Ribeiro et al, 2010. The overriding objective of these studies has been to identify those volatiles that are key contributors to the flavour of coffee.…”
Section: Determination Of Key Volatile Aroma Compounds In Coffeementioning
confidence: 99%
See 1 more Smart Citation